How the myobrace appliance works: Advantages and disadvantages - Paola da Cunha Busquet; Desirée de Jesus Portelinha; Monica Lage da Costa; Viviane de Andrade Cancio de Paula (Journal of Dental Problems and Solutions - Peertechz Publications, 2021)
Myofunctional Dentistry is a treatment that acts in the re-education of facial and masticatory muscles, correcting bad myofunctional habits such as mouth breathing, atypical swallowing and incorrect tongue positioning, directs the growth and correct development of the cranio-cervical-mandibular complex structures and helps in alignment and leveling of teeth in patients of all ages. Myobrace is a myofunctional device of Australian technology that promotes the correction of habits and dental alignment without the use of brackets. The objective of the work was to present a literature review of the Myobrace device. To this end, a survey was carried out in research bases (Medline, Cochrane, Embase, Pubmed, Lilacs and BBO) between the years 2019 and 2020, focusing on randomized clinical studies, prospective non-randomized longitudinal studies, systematic and meta-reviews analyzes, clinical cases that used Myobrace. As a result, after applying the inclusion and exclusion criteria, articles were found, which were used to carry out this work. It is concluded that orthodontic treatment cannot be considered a contributing factor for the development of temporomandibular disorders.